Water resources of the Desna river basin under future climate - Valeriy Osypov (IWA Publishing, 2021)
Climate change impact on water resources has been observed in Ukraine since the end of the 20th century. For now, only large-scale climate impact studies cover Ukraine's territory, having low credibility for a specific catchment. This study aims to calculate future changes in river discharge, water flow components, and soil water within the Desna basin and evaluate vulnerability trends on this basis. The framework assembles the process-based SWAT (Soil and Water Assessment Tool) model and eight high-resolution regional climate models (RCMs) driven by RCP4.5 and RCP8.5 emission scenarios. The climate models are provided by the Euro-CORDEX initiative and based on three RCMs (RCA4, HIRHAM5, and RACMO22E) forced by five general circulation models (CNRM-CM5, EC-EARTH, IPSL-CM5A-MR, HadGEM2-ES, and MPI-ESM-LR). The results preferably show a moderate increase in the annual discharge until the end of the 21st century. The intra-annual changes of water balance components negatively affect the vegetation period because of higher dryness and temperature stress but reduce flood risk, diffuse pollution, and water erosion in the far future. In the river basin management plan, the highest attention should be paid to adaptive strategies in agriculture because of possible water deficit in the vegetation season under future climate scenarios. HIGHLIGHTS The Desna river annual runoff as well as evapotranspiration will increase under an expected warmer and wetter climate.; Winter warming will reduce flood risk and increase groundwater flow during the year.; Soil water will significantly decrease in the vegetation period toward the end of the 21st century under RCP4.5 or RCP8.5.;